Employment in Manipur problems and prospects - Singh, Naghkham Ibatombi (Delhi Rajdhani Book Service, 2001)
Productive employment of the available labour force is the key to development of an economy.The present book is to examine existing nature of unemployment in different sectors of the economy and to identify the sector or areas where additional employment
Keywords: Manpower-India-Manipur; India-Manpower; Manipur (India)-Manpower; Employment-India-Manipur